1993
DOI: 10.1038/sj.bdj.4808157
|View full text |Cite
|
Sign up to set email alerts
|

The first 100 cases: a personal audit of orthodontic treatment assessed by the PAR (peer assessment rating) index

Abstract: The first 100 consecutively started cases treated by a specialist registrar in orthodontics were examined and pre- and post-study models were scored using the peer assessment rating (PAR) index. The PAR index proved both simple and reproducible to use: 92 cases had post-treatment records available, 91 patients registered a drop in PAR score, and one patient registered an increase. Of these 92 patients, 38 (41%) were greatly improved, 43 (47%) were improved, and 11 (12%) were made worse or no different (ie they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1
26

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 0 publications
3
22
1
26
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13] The paper of greatest relevance to the current audit is that by O'Brien et al in 1993, 5 in which the authors looked at 17 hospital departments and investigated some 1,392 cases treated with fixed appliances. They examined all cases, including those in which the appliances were removed early, and included all grades of operator.…”
Section: Setting a Standardmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] The paper of greatest relevance to the current audit is that by O'Brien et al in 1993, 5 in which the authors looked at 17 hospital departments and investigated some 1,392 cases treated with fixed appliances. They examined all cases, including those in which the appliances were removed early, and included all grades of operator.…”
Section: Setting a Standardmentioning
confidence: 99%
“…2,3 Experience with IOTN has shown that the need for treatment does not necessarily equate to the complexity of the treatment. It is important to make an assessment of complexity for the following clinical reasons (Richmond et al 4 …”
mentioning
confidence: 99%
“…The index is considered as a simple, objective and a reliable manner (19) for evaluating the stability after orthodontic treatment. Several studies have been conducted which demonstrate the method for assessing the stability after orthodontic treatment using the PAR index (1,2,9,12,17,21,22). According to the rules of the PAR index, each of the components of the dentition i.e.…”
Section: Par Index and Its Usementioning
confidence: 99%
“…There are basically three methods of assessing improvement using the PAR index (9,20 Centerline Score 0 -Coincident and upto one quarter lower incisor width 1 -One quarter to one half lower incisor width 2 -Greater than one half lower incisor width Tab. 5: Scores for recording the midline that are needed to assess the midline discrepancies.…”
Section: Par Index and Its Usementioning
confidence: 99%